Analysis of The Effectiveness of Implementing Tax Audit in Achieving Tax Revenue Target at The Enam Foreign Capital Investment Tax Services Office - Pandoyo; Noor, Chairani (CV ODIS, 2024)
This research was conducted to find out how much influence the effectiveness of tax audits has on achieving tax revenue targets at the Six Foreign Investment Tax Service Office. It is hoped that the achievement of the tax revenue target at the Sixth Foreign Investment Tax Service Office will be realized with the existence of a Tax Audit activity as supervision of taxpayers in fulfilling their tax obligations using the self-assessment method. The impact of increasing the effectiveness of tax audits will be directly proportional to the achievement of tax revenue targets. The benefit of this research is to increase knowledge for the writer and to provide input to the Six Foreign Investment Tax Service Office. This study uses a qualitative descriptive approach, by observing and interviewing informants who are considered to have mastered research problems. This study aims to determine the level of effectiveness of implementing tax audits in achieving the target of tax revenue at the Foreign Investment Tax Service Office Six. The method used in this study is a qualitative descriptive method that focuses on the effectiveness of tax audits by using an indicator of the amount of tax revenue targets determined by the realization of tax revenue achievement.